INVESTIGATION OF MEASURING SERIES IN GEODETIC WORKS - Akhmedov Bakhriddin Madaminovich (American Journals Publishing, 2023)
This article highlights the issues related to the research of measurement series to determine the accuracy of measurement results obtained under certain conditions, and the regularities of the distribution of errors.
Keywords: Geodetic instruments geodetic tools, true meaning, given accuracy, the distributions of the errors, equal-point and non-equal-point measurements, necessary and redundant measurement, the true error, studies of measurement series, mathematical expectation and standard, blunder, random and systematic errors.